PENGEMBANGAN EKONOMI ISLAM DAN RANCANG BANGUN EKONOMI ISLAM - Vera Ayu Oktoviasari; Fitri Apriani; Sumar’in (Jurnal Ekonomi dan Bisnis, 2024)
Islamic economics began to develop since the classical economic period in 738 AD - 1932 AD which was marked by the emergence of ideas such as Abu Yusuf with the book Al-Kharaj (Manual on Land Tax) and Abu Ubaid al-Qosim with the book 'Al-Amwal (The wealth). Then in 1058 AD-1466 AD, this economic development continued, colored by the thoughts of Ibn Khaldun as contained in the book Muqadimah. The rebirth of Islamic economics began with the awareness of Muslim scientists who assessed the need to restore Islamic teachings in everyday life. This awareness was an answer to the thoughts of contemporary Muslim scientists regarding economic problems which were deemed unable to be completely solved by the economic theory developing at that time. 70s. The research method used here is library research or literacy studies. Library research is a method of research where all activities are related to reading, recording and collecting library data and managing research materials. Meanwhile, literacy studies are a method of research which involves summarizing writings from books, journals and other documents, then describing the information and theories obtained, and organizing these libraries into discussion subchapters related to required topic. In this research, the type of data used by the author is data obtained from literature studies. The data that has been obtained is then analyzed using descriptive analysis methods. Islamic economics is likened to a house, building or structure that requires basic values, principles and concepts in the form of design before the economic system is built. By knowing an Islamic economic design, it is hoped that you can get a complete and comprehensive picture briefly about the Islamic economy which is like a building and consists of a roof, pillars and foundation. There are basic principles in Islamic economic design. These principles can generally be divided into three parts, namely: universal values, derivative principles and morals. The main principles held by Islamic economics are the principle of monotheism, the principle of justice and moral principles which are manifestations of the principle of nubuwah. These basic principles make Islamic economics superior to other economic systems, for example social or liberal economics.